The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/bog-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial development of sports facilities in Hungarian cities of county rank

Abstract: Abstract. Nowadays more and more attention is devoted to the spatial development of the location of sports facilities within cities. The main aim of our paper is to observe the most important spatial characteristics of their development in Hungarian cities of county rank. In these cities three main periods of development of sports facilities can be observed. Larger sports facilities were constructed especially on the edge of cities or in the suburbs, while in the case of smaller facilities a bigger role was pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
0
8
0
3
Order By: Relevance
“…Gábor Kozma (2014), in his work "The spatial development of sports facilities within the cities: a Central European case study", give special attention to spatial placement and development of sports facilities within localities.…”
Section: Global Evolution and Development Of The Areamentioning
confidence: 99%
“…Gábor Kozma (2014), in his work "The spatial development of sports facilities within the cities: a Central European case study", give special attention to spatial placement and development of sports facilities within localities.…”
Section: Global Evolution and Development Of The Areamentioning
confidence: 99%
“…The study of the relationship between sport and urban structures confirmed the importance of sustainable development of sport facilities (Li & Luk, 2011, European Commission, 2007. Kozma et al (2016) underlined the importance of the location of sports areas within cities and of the spatial development of sports facilities. Triantafyllidis & Davakos (2019) emphasized the importance of overcrowding, globalization and urbanization in people's lifestyles, stating that exercise leads to motivation, mental and physical wellbeing, community unity, confidence and sustainable consumer behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Main reason for this fact is that the location influences the sport-related activity of society and the performance of different teams (Rodríguez-Canamero et al, 2018;Chacon-Araya et al, 2018). The analyses show, on the one hand, the most important characteristics pertaining to the location of the facilities concerned within the settlements (Chapin, 2000;Estabrooks et al, 2003;Higgs et al, 2015;Kozma et al, 2016;Newsome & Comer, 2000;Thornley, 2002), and on the other hand, they also try to shed light on the differences between the settlements. From this latter point of view, one of the most important findings of the examination of the spatial distribution of leisure sports facilities was the identification of the differences between settlements of different sizes/locations/financial positions (Hallmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%